Key Trends and Prospects for sustainable Development of the Urban settlement system in the Russian Federation - R. V. Fattakhov; M. M. Nizamutdinov; Yu. S. Aitova; V. V. Oreshnikov (Финансы: теория и практика, 2021)
The subject of the study is the problem of the spatial distribution of the population in Russia and its regions. The relevance of research is determined by the key trends in the processes of distribution and movement of human capital in the context of cities. The paper aims to analyze the key trends and prospects for the development of the Russian settlement system at the federal, regional, and local levels. The research methods include a critical analysis of approaches to territorial settlement optimization, the modern system of urban settlement in Russia and its regions based on the use of statistical data of the Federal State Statistics Service for 2011-2019. The authors carried out a comparative analysis of the studied processes by countries using the Zipf method, as well as by Russian regions using the the Lorenz coefficient. It has been determined that the group of regions with an increase in the level of differentiation of urban settlement is characterized by a high level of depopulation of small and medium-sized cities with a contraction and concentration of the population in the largest city of the region, which creates additional risks for the sustainable development of the territory. A decrease in the level of differentiation of urban settlement is observed in regions where the share of the population of both small and medium-sized cities (but at a slower pace) and large ones is decreasing. The scientific novelty of the study lies in the development of an approach to improving the settlement system in Russia based on the application of the Lorenz coefficient and modelling methods. The authors conclude that an uneven system of settlement has developed in Russia, creating prerequisites for the emergence of new imbalances and threats to the complex sustainable development of the country’s territory. In this regard, it is advisable to develop an appropriate document in the field of state policy at the federal level or clarify similar issues within the framework of existing documents, as well as to increase the scientific validity of the measures taken using formalized methods of forecasting and planning. A promising direction in this area is the development of an agent-based model that allows increasing the efficiency of the distribution of financial resources for the development of social infrastructure. The results of the study justify the expediency of reallocating financial resources of the budget to ensure state policy in the field of development of the settlement system in the country.